Credibility in Peril: The Mismatch Between UK Foreign Policy and Capability in Deterring Aggression in the South Atlantic - Tilden, Philip J (2014)
Under the fiscal pressures presented by the recent recession, the latest British Strategic Defence and Security Review has been widely criticized for being finance rather than commitments led, in particular losing the carrier strike capability. This, coupled with a changing political landscape across South America and the significance of the Falkland Island (FI) Territories to Britain, suggests that a mismatch may now exist between national policy, strategy and resources. This mismatch will continue to be magnified as the Ministry of Defence is instructed to make further cuts in the coming years. This thesis aims to analyze the effectiveness of UK deterrence in relation to both British foreign policy and the current and potential future political landscape surrounding the FIs dispute. It will also aim to identify any disparity between desired influence and existing capability, making recommendations that will further inform the debate on maintaining a credible deterrence against potential aggression. The original document contains color images.